ROLLOVER STABILITY ANALYSIS OF LIQUID TANK TRUCK TAKING INTO ACCOUNT THE ROAD PROFILES - Tran, Van Nhu; Nguyen, Xuan Ngoc; Vu, Van Tan; Dang, Tien Phuc (Journal of Applied Engineering Science, 2022)
The rollover stability of the tank truck was quite poor compare with others due to the influence of the oscillating liquid inside the tank. In addition, it was also affected by road excitation during driving. Therefore, the paper presents the impact of the road profiles in turning and lane change maneuvers on the rollover stability characteristics of a liquid tank truck. Firstly, the study applies the quasi-static method and the roll model to built the dynamic model of a circular cross-section tank truck. After that, the Lagrange method and the D’Alembert’s principle are used to set up the differential equations which are then used to investigate rollover stability of vehicle corresponding with each liquid level. The research used the value of the load transfer ratio (LTR), crest factor of LTR and the roll angle of suspension to evaluate vehicle stability in the time domain and the transfer function magnitude of LTR in the frequency domain. The simulation results had shown that the tank truck tends to a rollover phenomenon at the fluid level in tank of 50% and 75% (0.8m and 1.2m) when the vehicle ran survey road profiles in a steady state turning maneuver and in a lane change maneuver as there was not the road excitation. The research results can provide recommendations when operating liquid tank truck, developing control systems and warning of rollover.